Cassava and Sweetpotato - What the Future Holds or "Quitely, the tuber fills...." Diam, diam, ubi berisi... - Tan, Swee Lian, author 300685; Academy of Sciences Malaysia 569766 (Kuala Lumpur : Akademi Sains Malaysia, 2010)
Includes bibliographical references and index